Family Bargaining and the Gender Gap in Informal Care - Chiara Canta; Helmuth Cremer (Institute of Labor Economics (IZA), 2022)
We study the optimal long-term care policy when informal care can be provided by children in exchange for monetary transfers by their elderly parents. We consider a bargaining model with single-child families. Daughters have a lower labor market wage and a lower bargaining power within the family with respect to sons. Consequently, they provide more informal care and have lower welfare in the laissez-faire (although not necessarily lower transfers). The first best involves redistribution from families with sons to families with daughters and can be implemented by a gender-specific schedule of public LTC benefits and transfers to working children. If the policy is restricted to be gender neutral, we find that the informal care provided by daughters should be distorted up to enhance redistribution from families with sons to families with daughters. Transfers within the family should be distorted in both types of families.
Keywords: D13; H23; H31; I19; 330; family bargaining; strategic bequests; informal care; long-term care; gender-neutrality